Sex Differences in the Predictors of Juvenile Delinquency: Females Are More Susceptible to Poor Environments; Males Are Influenced More by Low Self-Control. (February 2013) - Steketee, Majone; Junger, Marianne; Junger-Tas, Josine
The goal of the article is to investigate whether well-established risk factors for delinquency among adolescents are equally important for males and females. The risk factors discussed here are derived from four theoretical approaches: social bonding/social control theory, self-control theory, routine activities/opportunity theory, and social disorganization theory. Data are drawn from the International Self-Reported Delinquency study (ISRD-2). The results show that the risk factors proposed by social bonding theory, social disorganization theory, routine activities/opportunity theory, and self-control theory are not equally related to delinquent behavior among males and females. When all the theoretically relevant factors are combined together, three interaction terms are found to be statistically significant; family disruption and deviant behavior of friends have more influence on delinquent behavior of females, whereas the lack of self-control is more strongly related to delinquency among males.